Evaluation of blockchain-based crowdfunding campaign success factors based on vasma-l criteria weighting method - Santautė Venslavienė; Jelena Stankevičienė; Ingrida Leščauskienė (Administrative Sciences, 2023)
When investing in blockchain-based crowdfunding campaigns, choosing the right one is difficult. Therefore, it is important to recognize success factors that express the value of the specific campaign. This study is aimed at determining the success factors impacting the investors' decision to fund blockchain-based crowdfunding campaigns and ranking them according to their importance in decision-making. An online survey was employed to collect expert opinions. The modification of the visual analogue scale matrix for criteria weighting methodology called VASMA-L was presented in this study to rank the list of the predetermined factors. To reduce the uncertainties in the decision-making process and the cognitive overload of the survey respondents, all the predetermined success factors were split into two smaller groups and assessed as those that fit both traditional and blockchain-based crowdfunding models and those that are specific only to the blockchain-based crowdfunding model. The main findings disclose that the three factors with the highest VASMA weights are from the first group. This means that when selecting the specific crowdfunding campaign to invest in, investors use common factors rather than those specific to blockchain-based crowdfunding. Only investor preferences were chosen and analyzed for successful blockchain-based crowdfunding campaign investment in this research. The VASMA-L methodology might help compare several criteria groups and select the most important ones. In addition, this weighting methodology might help investors to choose the most thrilling blockchain-based crowdfunding campaigns to fund.
Keywords: 350; blockchain-based crowdfunding; blockchain-based crowdfunding campaign; funding; risk; success factors; VASMA weighting; VASMA-L